Methodological guidelines for tracking public spending on agriculture with illustrations from Zambia - Govereh, Jones; Malawo, Emma; Jayne, Thomas S.; Chilonda, Pius (International Food Policy Research Institute, 2008)
Public spending on agriculture needs to be traced to learn how much is being spent, where it is being spent, what it is being spent on and for whom, and how it has changed over time. Spending on agriculture includes all spending on activities whose primary purpose is to restore, improve and maintain agriculture for the nation and for individuals in a given time period regardless of the institution or entity providing for the activity. This guide provides a framework for tracking public spending on agriculture. Measuring public spending on agriculture will make it possible to debate the size and quality of allocation and subsequently improve public resource use efficiency. Achieving agricultural development targets requires good public resource management which can only be done with good reliable spending accounts.